Applied Process Design For Chemical and Petrochemical Plants - Ludwig, Ernest E. (Gulf, 1991)
Contiene: Process Planning, Scheduling, Flowsheet Design; Fluid Flow; Pumping of liquids; Mechanical Separations; Mixing of Liquids; Ejector and Vacuum Systems; Pressure-Relieving Devices; Appendix of Conversion Factors.